2020
DOI: 10.11606/issn.2316-9095.v20-160040
|View full text |Cite
|
Sign up to set email alerts
|

Petrologia e idade do Stock Fazenda Lagoas, Domínio Macururé, Sistema Orogênico Sergipano, NE-Brasil

Abstract: Disponível on-line no endereço www.igc.usp.br/geologiausp -39 - Resumo O Stock Fazenda Lagoas (SFL), com 20 km 2 , tem idade de cristalização de 623 ± 4 Ma e é intrusivo nas rochas metassedimentares do Domínio Macururé (DM). O seu contato ao norte é afetado pela Zona de Cisalhamento Belo Monte-Jeremoabo (ZCBMJ), que imprime estrutura gnáissica às rochas desse stock. O SFL é essencialmente constituído de quartzo monzonitos, tendo monzogranitos e granodioritos subordinados. Os enclaves microgranulares são abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(43 reference statements)
0
4
0
1
Order By: Relevance
“…In the SOS, MEs are found mainly in intrusions of the Macururé and Poço Redondo domains, such as in the Glória Norte Stock (Lisboa et al 2019), Curituba Batholith (Gentil 2013, Lima 2016, Lagoa do Roçado Stock (Silva 2014), Monte Alegre Stock (Oliveira 2014), Glória Sul Stock (Conceição et al 2016), Fazenda Lagoas Stock (Fernandes et al 2020), RJB (Sousa et al 2019), andCapela Stock (Pereira et al 2019). Many of these plutons are more than 10 km apart and have ages varying from 631 to 588 Ma.…”
Section: Magma Of the Microgranular Enclavesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the SOS, MEs are found mainly in intrusions of the Macururé and Poço Redondo domains, such as in the Glória Norte Stock (Lisboa et al 2019), Curituba Batholith (Gentil 2013, Lima 2016, Lagoa do Roçado Stock (Silva 2014), Monte Alegre Stock (Oliveira 2014), Glória Sul Stock (Conceição et al 2016), Fazenda Lagoas Stock (Fernandes et al 2020), RJB (Sousa et al 2019), andCapela Stock (Pereira et al 2019). Many of these plutons are more than 10 km apart and have ages varying from 631 to 588 Ma.…”
Section: Magma Of the Microgranular Enclavesmentioning
confidence: 99%
“…In the Sergipano Orogenic System (SOS; Conceição et al 2016), there is evidence of voluminous Neoproterozoic plutonism that has been the target of several studies over the last few decades (e.g., Santos and Souza 1988, Davison and Santos 1989, Santos et al 2001, Bueno et al 2009, Oliveira 2014, Oliveira et al 2015, Conceição et al 2016, Fontes et al 2018, Lisboa et al 2019, Pinho Neto et al 2019, Santos et al 2019, Sousa et al 2019, Fernandes et al 2020. Many of these studies identified the presence of MEs in these intrusions; however geological, petrographic, and geochemical data from MEs in the SOS are still scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…de cisalhamento Macururé (ZCM), Belo Monte-Jeremoabo (ZCBMJ), São Miguel do Aleixo (ZCSMA) e Itaporanga (ZCI). Os Domínios Estância, Vaza-Barris e Macururé são constituídos predominantemente por rochas metassedimentares, ocorrendo, no último, vários corpos graníticos neoproterozoicos (Lisboa et al, 2019;Santos et al, 2019;Pereira et al, 2019;Fernandes et al, 2020). O Domínio Poço Redondo-Marancó, constituído pelos Subdomínios Poço Redondo e Marancó, é composto por rochas metavulcanossedimentares (Davison e Santos, 1989;Oliveira et al, 2010Oliveira et al, , 2017.…”
Section: Contexto Geológicounclassified